EFFICACY OF DIFFERENT TREATMENT MODALITIES USED IN EPISTAXIS (Iraqi Journal of Medical Sciences, 2016)
Background: This is a cross-sectional, clinical study, implemented in the Department of Otolaryngology / Sulaimani Teaching Hospital; from July 15th 2004 to April 15th 2005. Objectives: The aim of the study is to describe the demographic characteristics, aetiological factors and therapeutic measures for epistaxis in Sulaimani region, to improve our experience in the management of this common condition. Methods: This study included 100 patients of different age and sex who attended ENT department during the period of the study.Results: At the end of the study we found that most cases of epistaxis can be treated by simple measures like application of lubricants to nose, or cauterization and anterior packing.Conclusion: Active intervention should be done when indicated.Keywords: epistaxis, lubricants, cauterization, anterior packing, active intervention.
Keywords: epistaxis; lubricants; cauterization; anterior packing; active intervention